Respuesta :

1. Find the slope using the slope formula.
[tex] \frac{2 - ( - 4)}{ - 1 - 1} = \frac{2 + 4}{ - 2} = - \frac{6}{2} = - \frac{3}{1} = - 3[/tex]
2. Plug that slope and either point into an equation in slope-intercept form and solve for b.
[tex]2 = - 3( - 1) + b \\ 2 = 3 + b \\ - 1 = b[/tex]
3. Now write your answer as a slope-intercept form equation
[tex]y = - 3x - 1[/tex]
cher
Slope-intercept form : y=mx+b ; where m=slope, b=y-intercept

Passes through (-1, 2) as well as (1, -4)

Our first step is to find the slope. So, using the slope formula, let's get started! :)

Slope formula : m = y₂-y₁ / x₂-x₁

y₂ = -4 ; y₁ = 2 ; x₂ = 1 ; x₁ = -1

So, let's plug in our values! :)

m = y₂-y₁/x₂-x₁ → m = -4 - (2) / 1 - (-1)

Simplify.

m = -4 - 2 / 1 + 1

Simplify.

m = -6 / 2

Simplify.

m = -3

Now choose a set of points - I chose (-1, 2)

Now with those points, plug those points (and slope) into slope intercept form

y = mx + b

(2) = -3(-1) + b

Simplify.

2 = 3 + b

Now we have to isolate b - simply subtract 3 from both sides.

2 -3 = b

b = -1

Now we have our b value!

**Remember : m = -3, b = -1**

So now we just need to plug these into slope intercept form :)

y = mx + b

y = -3x - 1

~Hope I helped!~


ACCESS MORE